Design of a versatile nanocomposite for 'seeing' drug release and action behavior. Issue 43 (2nd September 2015) - Zhang, Yu; Shen, Tingting; Deng, Xia; Ma, Yufei; Wang, Lina; Peng, Yong; Wu, Jiang; Zhang, Zhijun; Liu, Weisheng; Tang, Yu
Abstract : To design a new method for 'seeing' drug release and action behavior, we combined a rare-earth complex with a magnetic-core-coated phenyl mesoporous silica nanoparticles matrix, taking advantage of the drug coordination for real-time monitoring. Abstract : The capability of monitoring drug release and its action behavior is crucial for understanding the quantitative information regarding drug biodistribution and pharmacokinetic studies. Herein, for the first time, based on the coordination characteristics of rare-earth (RE) ions, including the exchangeable and extendable coordination sphere and their susceptible photoluminescence (PL) intensity to the surrounding coordination environment, we propose a novel concept of drug coordination for the real-time monitoring of drug release using the PL emissions of RE complexes. We chose magnetic-core-coated phenyl mesoporous silica nanoparticles (phMSNs) as the matrix to constrain the Eu(iii ) complex by strong π–π interactions and hydrophobic property. When the drug was loaded into the channels of the phMSNs shell by the coordination effect, the PL intensity of the Eu(iii ) complex was enhanced drastically because of the inhibition of energy transfer (ET) from the Eu(iii ) complex to the shell of phMSNs due to the coordination effect between the drug molecules and Eu(iii ) ions. Moreover, real-time monitoring could be realized by the recovering of ET with the release of the drug. Most importantly, the Fe3 O4 core provides a visualization function for the nanocomposite using the atomic-resolution TEM techniques for finding the precise drug action sites and for elucidating the anticancer action mechanism. As we demonstrated, the nanocomposite killed HeLa cells mainly by attacking their nuclear membranes and nuclei. Therefore, the design of the nanocomposite with an integral composition could be suitable for use with existing clinical applications to determine online the drug concentrations in the tissue regions of interest and drug action behavior in real-time.